Synthesis of 5-Iodo-1,2,3-triazoles from Organic Azides and Terminal Alkynes: Ligand Acceleration Effect, Substrate Scope, and Mechanistic Insights - Barsoum, David N.; Brassard, Christopher J.; Deeb, Jason H. A.; Okashah, Najeah; Sreenath, Kesavapillai; Simmons, J. Tyler; Zhu, Lei (Synthesis, 2013)
An improved method has been developed for the preparation of 5-iodo-1,2,3-triazoles directly from organic azides and terminal alkynes by a reaction mediated by copper(I) and iodinating agents generated in situ. The major methodological advance of the current procedure is that it provides a high conversion and good iodo/proto selectivity with a broad range of substrates without using an excess of the alkyne, which was required in the previous method. The use of an accelerating ligand is essential to the success of reactions involving unreactive azides or alkynes. New mechanistic insights are provided, including the confirmation that a 1-iodoalkyne is formed as a key intermediate under the established conditions for the reaction.
Keywords: azides; alkynes; copper; catalysis; heterocycles; cyclizations; triazoles; halogenation; iodine